Faktor Pengaruh Kepuasan Pengguna Aplikasi Elnino Dalam Rangka Pembelajaran Daring Menggunakan Metode End User Computing Satisfaction - Budhi Adhiani Christina; Sumanto Sumanto; Mardinawat Mardinawat; Teguh Budhi Santosa; Maharani Rona Makom (JEMAP, 2022)
This research is conducted to verify the effect of content (isi), accuracy (akurasi), format (bentuk), ease of use (kemudahan pemakaian), and timeliness (ketepatan waktu) toward the satisfaction of ELNINO application users in Accountant major Polines. The method used in this research is End User Computing Satisfaction (EUCS) with independent variables which consist of content (isi), accuracy (akurasi), format (bentuk), ease of use (kemudahan pemakaian), timeliness (ketepatan waktu), and dependent variable that is user satisfaction. This research is quantitative research using primer and secondary data. Data collection is done with questionnaire and literature review method. The target in this research is students majoring in Accounting in Politeknik Negeri Semarang. In taking samples, this research uses the technique of simple random sampling and the sample used is 100 respondents. The analytical method used in testing the hypothesis is multiple linear regression. The results from this research show that the variables of content, accuracy, ease of use, and timeliness influence user satisfaction of the ELNINO application, whereas the variable format has no effect on user satisfaction of the ELNINO application. In addition, it is found that the variables of content, accuracy, format, ease of use, and timeliness simultaneously affect the satisfaction of ELNINO application users.